1993
DOI: 10.1164/ajrccm/148.6_pt_1.1558
|View full text |Cite
|
Sign up to set email alerts
|

Serum Type III Procollagen Peptide in Patients withPneumocystis cariniiInfection

Abstract: Inflammation may play a central role in the pathogenesis of HIV-related Pneumocystis carinii pneumonia (PCP). Serum levels of the amino-terminal propeptide of Type III procollagen (PIIINP) reflect inflammatory activity in granulation tissue and in chronic rheumatic and liver disorders. To investigate changes in PIIINP serum levels during an episode of HIV-related PCP, consecutive serum samples were taken from 48 HIV-infected patients with PCP in a randomized, placebo-controlled study of the effect of adjunctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Published research showed that in hypertensive heart failure patients with elevated cardiac filling pressures, an increase in circulating TIMP-1 levels relative to MMP1 levels suggested ongoing collagen synthesis (11). Several studies have shown that cardiac fibrosis histology measures are associated with circulating fibrosis biomarkers (12,13). These and other data established that excessive collagen metabolism due to progressive vascular remodeling plays a distinct role in the pathophysiology of PAH and that collagen content of a tissue may be assessed with the serum analysis of breakdown products of collagen.…”
Section: A Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published research showed that in hypertensive heart failure patients with elevated cardiac filling pressures, an increase in circulating TIMP-1 levels relative to MMP1 levels suggested ongoing collagen synthesis (11). Several studies have shown that cardiac fibrosis histology measures are associated with circulating fibrosis biomarkers (12,13). These and other data established that excessive collagen metabolism due to progressive vascular remodeling plays a distinct role in the pathophysiology of PAH and that collagen content of a tissue may be assessed with the serum analysis of breakdown products of collagen.…”
Section: A Methodsmentioning
confidence: 99%
“…Studies show that the transpulmonary gradient of procollagen III occur in normal subjects undergoing cardiac catheterization suggesting that normal human lungs can actively synthesize collagen (9). It has been established that elevated procollagen III levels in the serum mirror changes in bronchoalveolar lavage of patients with sarcoidosis (10), interstitial pulmonary fibrosis (11), pneumocystis carinii pneumonia (12), acute lung injury (13), and acute respiratory distress syndrome (14,15) indicating that such parenchymal changes are reflected in peripheral blood samples. These studies suggest that ongoing collagen metabolism in the pulmonary vascular can be assessed by measuring circulating levels of collagen metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The significant correlation detected during therapy among these variables indicates a likely casual link between reduction in fibrogenesis and resolution of pulmonary and extrapulmonary organ dysfunction. Two prior clinical reports have described a reduction in circulatory PIIINP levels during prolonged glucocorticoid treatment of patients with usual interstitial pneumonitis (16), and pneumocystis pneumonia (44). Both studies found that a reduction in circulatory peptide levels correlated with improvement in lung physiology (16,44).…”
Section: Changes During Methylprednisolone Treatmentmentioning
confidence: 94%
“…Adjuvant corticosteroid therapy has reduced the overall mortality rate among moderately severe cases by 40%[41]. Several markers of disease severity are associated with outcome, including arterial oxygenation, serum lactate dehydrogenase, BAL neutrophilia, BAL IL‐8, and PIIINP (a marker of activation and overall inflammation) [42–48].…”
Section: Perspective and Conclusionmentioning
confidence: 99%